Plan De Importación y Comercialización De Repuestos y Accesorios Para Ordenadores Para Una Tienda Virtual. (2023)
In this research plan, an international business project was designed with the aim of simulating from beginning to end the import and commercialization process from China to Colombia of spare parts and accessories for computers. In addition, demonstrate the knowledge acquired during the undergraduate international trade program. Several stages were developed in order to know the project viability including the market, technical, administrative, legal, financial, and economic studies.